Qualidade fisiológica de sementes de soja enriquecidas com molibdênio - Possenti, Jean Carlo (2007)
To compare the physiological quality of soybeans seeds that had been enriched with molybdenum with not enriched seeds, and the application the element at seedling, this experiment was divided in two years. In the first year of the experiment, seeds of three soybean varieties CD-206, MSOY-7101 and BRS-183, had been enriched with Mo the application of 800 g.ha -1 of molybdenum, divided in two foliage applications, of the same dose. One, in the phase R3 and the other one, in the phase of R5. After harvesting it was evaluated productivity and the weight of a thousand seeds and after seed processing, it was evaluated germination, field emergency, accelerated aging and the conductivity test for zero, three and six months of storage. In the second year of the experiment, two varieties, CD-206 and BRS-183, that came from the seeds enriched in the previous year with Mo had been submitted to the application in the dose of 20 g.ha -1 . After harvesting, it was evaluated productivity, weight of a thousand seeds and after seeds processing, it was determined germination, field emergency, accelerated aging and the conductivity test. It was concluded that the seed produced the application of Mo in high doses during the phases of R3 and R5, presents high concentrations of the nutrient, however, it does not transfer the same concentration of the nutrient to the seed of the next generation and the enrichment of soybeans seeds with Mo does not affect the physiological quality of seeds, the yield components.